BENTUK PEMBELAJARAN KHUSUS UNTUK ANAK BERKEBUTUHAN KHUSUS BERSIFAT SEMENTARA DI RA SYIHABUDDIN - Fanani, Ila Rokhmatul (Jurnal Penelitian Anak Usia Dini, 2024)
This study aims to determine the use of individual learning forms for temporary ABK at RA Syihabuddin Dau Malang. The background to this research concerns the issue of special education for children with special needs at RA Syihabuddin using individual learning created independently by the school. The research method used in this research is a qualitative method with a case study type of research because there is only one subject to be studied. Data collection techniques used were interviews, observation and documentation. while the data analysis techniques used are data reduction, data presentation, and drawing conclusions. Data validity testing uses the triangulation method of interviews, observation and documentation to obtain accurate comparisons.Based on the results of research conducted by researchers, it was concluded that the stages of planning Individual Learning Forms for ABK carried out by RA Syihabuddin only went through two stages, namely recommendation and placement. After planning, the conclusion in implementing the Individual Learning Form for ABK is carried out in accordance with the Individual Learning Form procedure for ABK where learning activities are carried out individually by the shadow teacher but also by paying attention to collaboration with the teacher. Furthermore, learning evaluation is carried out by continuing the activity when the next activity has been achieved and repeating the previous activity if it has not been achieved in accordance with the implementation of the individual specific learning evaluation.